Estado nutricional y su relación con el desarrollo psicomotor en preescolares de la I.E.I 329 Mi Mundo Feliz- Punchana 2023 - Tantaleán Mozombite, Diana Carolina (2024)
This study aimed to determine the relationship between nutritional status and psychomotor development in preschools of the I.E.I 329 Mi Mundo Feliz-Punchana 2023. It was a quantitative approach, not experimental, with descriptive, correlational design with a transversal character, with a total of 108 preschoolers aged between 3 and 5 years, 56 boys and 52 women. By taking size and weight, the nutritional status was determined and for psychomotor development a TEPSI test was used. In relation to the nutritional status in the P/E indicator, 90.7% of preschoolers had normal P/E, 7.4% overweight and 1.9% malnutrition. In the T/E indicator, 84.2% had normal T/E, 9.3% high size and 6.5% low size. In the P/T indicator, 77.8% had normal P/T, 10.1% malnutrition, 7.4% obesity, 2.8% overweight and 1.9% severe malnutrition. In psychomotor development, in the coordination subtest, 89.8% of preschoolers presented normal coordination, 5.6% delay and 4.6% risk. In the language subtest, 91.7% presented normal language, 5.6% risk and 2.8% delay. In the motricity subtest, 96% of preschoolers had normal motor skills, 2.8% risk and 0.9% retardation. By associating the P/E indicator with the language subtest, a statistically significant relationship was found with a bilateral 0.01 significance level, but when associating it with the coordination subtest, no significant relationship was found. By associating the T/E indicator, a significant relationship was found with the language subtest with a bilateral significance level of 0.05 and motor skills with a significance level of 95% (p<0.05). However, when associating it with the coordination subtest, no significant relationship was found. By associating P/T with the subtest of coordination, language and motor skills, a significant relationship with a bilateral 0.01 significance level was found. The study concludes by affirming a significant relationship between nutritional status and psychomotor development in preschoolers who attend the I.E.I 329 My Happy World-Punchana 2023.